Closed‐End Fund Shares' Abnormal Returns and the Information Content of Discounts and Premiums - BRAUER, GREGGORY A. (Journal of Finance, 1988)
ABSTRACT Closed‐end funds' discounts contain information in the sense that they can be used to construct portfolios that earn returns exceeding those predicted by the two‐factor capital asset pricing model. The precise nature of the information contained in a discount is not clear, however. This paper provides evidence that the information contained in a discount is an incomplete prediction of the fund's likelihood of being open‐ended profitably.